Analisis Leverage, ROA, dan CE Index pada Emiten yang Melakukan Merger dan Akuisisi di Perusahaan Publik Indonesia - Saiful Bahgia; Sriwinarsih Ramadhana; Rahmaniar; Cut Intan (Paraduta : Jurnal Ekonomi dan Ilmu-Ilmu Sosial, 2026)
The This study aims to describe the conditions of leverage, profitability (Return on Assets/ROA), and circular economy implementation (Circular Economy Index/CE Index) among companies conducting mergers and acquisitions (M&A) listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A quantitative descriptive method was employed with a purposive sample of 20 M&A companies listed on the IDX that possessed complete financial statement and sustainability report data throughout the observation period. Leverage and ROA data were obtained from annual financial reports, while the CE Index was constructed through a weighted scoring of three sub-components, namely Resource Efficiency, Waste and Emission Reduction, and Environmental Performance, based on the Global Reporting Initiative (GRI) framework. The results indicate that the average leverage of M&A companies stood at 51.20% with an increasing trend, reflecting the dominance of debt financing in acquisition transactions. The average ROA of 4.96% (after outlier adjustment) was unstable and varied widely across sectors, confirming that M&A synergies do not necessarily materialize in the short term. Meanwhile, the CE Index demonstrated the most consistent upward trend throughout the observation period, rising from 11.29% to 15.85%, indicating continuous improvement in circular economy implementation driven by sustainability regulatory compliance. Descriptive patterns further reveal that companies with higher CE Index scores tend to exhibit above-average ROA, opening avenues for inferential exploration in future research. These findings contribute to the understanding of financial behavior and sustainability practices among M&A companies in Indonesia, while providing an empirical basis for further research on the causal relationships between capital structure, circular economy performance, and corporate profitability